Predictive system-level modeling framework for transient operation and cathode platinum degradation of high temperature proton exchange membrane fuel cells. (1st April 2020) - Kregar, Ambrož; Tavčar, Gregor; Kravos, Andraž; Katrašnik, Tomaž
Graphical abstract: Highlights: Coupled system-level model of fuel cell operation and degradation is developed. Operation of fuel cell is simulated with a mechanistic spatially and temporally resolved model. Transient platinum degradation modeling framework simulates particle size redistribution. Platinum oxidation, dissolution, precipitation, detachment and agglomeration is modeled. Credibility of the model is confirmed by remarkable agreement with the experimental data. Abstract: High temperature proton exchange membrane fuel cells (HT-PEMFCs) are a promising and emerging technology, which enable highly efficient, low-emission, small-scale electricity and heat generation. The simultaneous reduction in production costs and prolongation of service life are considered as major challenges toward their wider market adoption, which calls for the application of predictive virtual tools during their development process. To present significant progress in the addressed area, this paper introduces an innovative real-time capable system-level modeling framework based on the following: (a) a mechanistic spatially and temporally resolved model of HT-PEMFC operation, and (b) a degradation modeling framework based on interacting individual cathode platinum degradation mechanisms. Additional innovative contributions arise from a consistent consideration of the varying particle size distribution in the transient fuel cell operating regime. The degradation modeling framework interactively considers the carbon and platinum oxidation phenomena, and platinum dissolution, redeposition, detachment, and agglomeration; hence, covering the entire causal chain of these phenomena. Presented results confirm capability of the modeling framework to accurately simulate the platinum particle size redistribution. Results clearly indicate more pronounced platinum particle growth towards the end of the channel since humidity is the main precursor of oxidation reactions. In addition, innovative modeling framework elucidate contributions of agglomeration, which is more pronounced at voltage cycling, and Ostwald ripening, which is more pronounced at higher voltages, to the platinum particles growth. These functionalities position the proposed modeling framework as a beyond state-of-the-art tool for model-supported development of the advanced clean energy conversion technologies.